PELATIHAN PEMANFAATAN CHATGPT DALAM PENULISAN KARYA ILMIAH UNTUK MENINGKATKAN KOMPETENSI PUBLIKASI DOSEN UNIVERSITAS BINA BANGSA GETSEMPENA - Syarfuni Syarfuni; Verawati Verawati (Jurnal Pengabdian Pemersatu Bangsa, 2026)
The scientific publication competence of lecturers is an important indicator in improving the quality of higher education. However, many lecturers still face obstacles in writing scientific papers that meet publication standards, particularly in the aspects of idea development, article structure, and the use of academic language. This community service activity aims to improve the publication competence of lecturers at the Faculty of Teacher Training and Education (FKIP) at Bina Bangsa Getsempena University through training on the use of ChatGPT as a companion in writing scientific papers. The methods used included material delivery, demonstrations, hands-on practice, discussions, and assistance in writing scientific articles. The results of the activity showed that participants were able to use ChatGPT more effectively to develop research ideas, develop article outlines, improve the quality of academic language, and increase their understanding of the ethical use of artificial intelligence in scientific writing. This training made a positive contribution to improving lecturers' readiness to produce higher-quality scientific publications.